Innovation in Idli batter preservation through betel leaf essential oil-based nanoemulsion: Evaluating fermentation kinetics and physicochemical analysis - Sangeetha Karunanithi; Proshanta Guha; Prem Prakash Srivastav (Food Chemistry Advances)
Extending shelf life while maintaining quality of traditional fermented foods is a major challenge. This study aimed to investigate betel leaf essential oil nanoemulsions (BLEONE) as a clean-label preservative for fermented Idli batter. BLEONE (1–10 %) was incorporated into Idli batter and evaluated for physicochemical properties, sensory quality, and shelf life during ambient (30 °C) and refrigerated (4 °C) storage. Kinetic modeling and analysis of variance (ANOVA) were used to quantify BLEONE's effects on fermentation dynamics and assess statistical significance. At 5 % concentration, BLEONE significantly (p < 0.05) maintained pH (4.5 vs 3.8 in control), restricted acidity increases (1.2 % vs 1.8 % in control), and limited viscosity loss (15 % vs 40 % in control) during fermentation compared to untreated and sodium benzoate-treated samples. Sensory analysis showed acceptable attributes up to 5 % BLEONE. Optimally fermented Idli batter with 5 % BLEONE extended shelf-life to 7 days at 30 °C and 25 days at 4 °C storage. The nanoemulsion's enhanced antimicrobial efficacy and controlled release of active compounds significantly improved safety and quality preservation during storage. This research demonstrates the potential of essential oil nanoemulsions as effective clean-label preservatives for traditional fermented foods, offering a promising solution to extend shelf life while maintaining product quality.